Combination of Chitosan from Black Soldier Fly Exuviae and Palm Oil Stearin as Coating on Chicken Eggs - Muheri Indra Aja Nasution; Yaya Rukayadi (Jurnal Peternakan Integratif, 2026)
Consumption chicken eggs have perishable properties, the quality of eggs will decline faster and the shelf life of eggs is very short at room temperature compared to cold temperatures. The purpose of this study is to test and evaluate the use of chitosan derived from black soldier fly exuviae and palm oil stearin as a coating on the quality of consumption chicken eggs at room temperature storage. Study design was a Completely Randomized Design (CRD) 4 x 5 factorial pattern with three replications. Each replicate consisted of 6 fresh chicken eggs, resulting in 360 eggs. Factor I was formula dosage (CS0 = Without Coating; CS1 = Virgin Coconut Oil; CS2 = 1.5% Chitosan + 1% Stearin; CS3 = 3% Chitosan + 1% Stearin) and Factor II was storage duration (ST0 = 0 Days; ST14 = 14 Days; ST28 = 28 Days; ST42 = 42 Days; ST56 = 56 Days). The results of the study indicate that the formula dose and storage time had a very significant effect (P<0.01) on the Haugh unit, albumen index, and yolk index of consumption chicken eggs. There was an interaction between the formula dose and storage time (P<0.01) on the Haugh unit, albumen index, and yolk index. Coating combination of chitosan BSF exuviae and palm oil stearin can maintain the quality of consumption chicken eggs during the storage period up to 56 days. The use of a coating formula with a treatment level of 3% chitosan + 1% stearin showed the best results in maintaining the quality of consumption chicken eggs during storage at room temperature and was still in quality category III according to SNI No.3926:2023, namely haugh unit 60.54%, albumen index 0.06% and yolk index 0.33%.